An urban techno-economic hydrogen penetration scenario analysis for Burdur, Turkey - UYAR, TANAY SIDKI (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
In this paper, the current energy mix and the power generation infrastructure of Turkey have been analyzed and two different hydrogen based alternative scenarios applied on Burdur TIMES energy model to foresee the economic and environmental results in the 2016-2031 time period. An improved RES was created to illustrate the current energy network of Burdur city and to determine the relationships between energy carriers and the respective technologies, and then this structure is specified by the relevant data, including fuel cell-powered land vehicle technologies integrated into the land transportation demand side. This paper analyses the feasibility of hydrogen as an alternative energy carrier in the fuel mix for electricity generation in Burdur City to achieve sustainable economic growth, to improve the energy security by minimizing respective environmental emissions and indicate the possible implications of the introduction of the hydrogen supply chain and respective fuel cell end-use technologies in a city level energy modelling perspective. Burdur is selected as the target city to implement the designated level of land transport passenger demand by hydrogen technologies; and after implementation of hydrogen cars in 2020; it has been evaluated that only 0.09 PJ of hydrogen car activity prevents a total of 43.44 kT CO2 emission in Burdur, addressing the 8% of the total emission in the base scenario between the analysis time horizon. Finally, hydrogen has been evaluated as a clean, dependable option to diversify the energy mix on the current energy supply system of Burdur. (C) 2019 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Urban energy system modelling; Hydrogen; Answer-TIMES; Burdur; Turkey; ENVIRONMENTAL-IMPACT ASSESSMENT; MULTIGENERATION SYSTEM; THERMAL MANAGEMENT; INTEGRATED-SYSTEM; ENERGY; POWER; OPTIMIZATION; BATTERY; MODEL; CYCLE